Alleviation of Aflatoxin B1‐Induced Genomic Damage by Proanthocyanidins via Modulation of DNA Repair. Issue 11 (15th June 2016) - Bakheet, Saleh A.; Alhuraishi, Ahmed M.; Al‐Harbi, Naif O.; Al‐Hosaini, Khaled A.; Al‐Sharary, Shakir D.; Attia, Mohammed M.; Alhoshani, Ali R.; Al‐Shabanah, Othman A.; Al‐Harbi, Mohammed M.; Imam, Faisal; Ahmad, Sheikh F.; Attia, Sabry M.
ABSTRACT: In order to study the mechanisms underlying the alleviation of aflatoxin B1‐induced genomic damage by proanthocyanidins (PAs), we examined the modulation of oxidative DNA damage induced by aflatoxin B1 in PAs‐pretreated animals. The effects of PAs on changes in the expression of DNA damage and repair genes induced by aflatoxin B1 were also evaluated in rat marrow cells. Administration of PAs before aflatoxin B1 significantly mitigated aflatoxin B1‐induced oxidative DNA damage in a dose‐dependent manner. Aflatoxin B1 treatment induced significant alterations in the expression of specific DNA repair genes, and the pre‐treatment of rats with PAs ameliorated the altered expression of these genes. Conclusively, PAs protect against aflatoxin B1‐induced oxidative DNA damage in rats. These protective effects are attributed to the antioxidant effects of PA and enhanced DNA repair through modulation of DNA repair gene expression. Therefore, PAs are a promising chemoprotective agent for averting genotoxic risks associated with aflatoxin B1 exposure.